A Conceptual Study of Startup India - A Rejuvenation - Mittal, Bhawna; Garg, Shubhra (Journal of Commerce and Trade, 2018)
Scott Belsky once said that It's not about ideas, rather it's all about making ideas happen. It is a well-known fact that for a Startup to flourish only 20 per cent of the idea is required; rest 80 per cent of the work is of execution. In the age of emerging Start Ups, when the competition is at its peak, it becomes difficult for companies to rise. Though India continues to harbor the third largest startup base in the world, the challenges range from cash flow to family support and to choosing right investors and so on. This research paper revolves around the concept of Start Up India Campaign, brought into existence by Shri Narender Modi, Prime Minister on 15th August 2015. The basic purpose of this paper is to throw light on the initiative taken by the government and to discuss the policies, plans, strategies and related schemes. We will also discuss about the roadblocks faced by our young entrepreneurs and the possible outcomes of the same. Classification-JEL : L16, O14, O38